Antibiotics in surgical wards: use or misuse? A newly industrialized country’s perspective - Mun Kit Lim; Pauline Siew Mei Lai; Sasheela Sri La Sri Ponnampalavanar; Sharifah Faridah Syed Omar; Nur Aishah Taib; Mohamad Yasim Yusof; Claire Marie Italiano; David Chee Ming Kong; Adeeba Kamarulzaman (Journal of Infection in Developing Countries)
Introduction: Studies exploring the appropriateness of therapeutic antibiotic use among surgical patients are limited, particularly in developing countries. Therefore, the aim of our study was to determine the appropriateness of antibiotics prescribed in a surgical setting in Malaysia. Methodology: A prospective observational study was conducted in two surgical wards at a tertiary hospital in Malaysia from November 2012-July 2013. Data was collected using a case report form. The appropriateness of antibiotic therapy was based on compliance with either the Malaysian National Antibiotic Guidelines 2008 or International Clinical Practice Guidelines and determined by an expert panel (consisting of two infectious disease consultants and a pharmacist). Results: Over the study period, a total of 593 antibiotic courses were prescribed for 129 patients (4.6±3.4 antibiotics/patient). Only 34 (26.4%) patients received appropriate antibiotic therapy, whilst 95 (73.6%) patients received at least one course of inappropriate antibiotic therapy. The prevalence of inappropriate antibiotic use was 214 (66.3%) and 55 (42.0%) for prophylactic and therapeutic purposes, respectively. The most common causes of inappropriate prophylactic antibiotics were inappropriate timing 20 (36.4%) and inappropriate duration of prophylaxis 19 (34.5%). In cases of inappropriate timing, 9 (45%) were administered too late while 6 (30%) were too early. . In contrast, inappropriate choice of antibiotics (42.1%) and inappropriate indication (40.7%) were the most common reasons encountered for inappropriate therapeutic antibiotics. Conclusion: Our study suggests considerable inappropriate use of both prophylactic and therapeutic antibiotics in the surgical wards; highlighting an urgent need for antibiotic stewardship initiatives in this setting.